Supramolecular Recognition Influences Magnetism in [X@HVIV8VV14O54]6− Self‐Assemblies with Symmetry‐Breaking Guest Anions. Issue 6 (17th November 2014) - Yu. Monakhov, Kirill; Linnenberg, Oliver; Kozłowski, Piotr; van Leusen, Jan; Besson, Claire; Secker, Tim; Ellern, Arkady; López, Xavier; Poblet, Josep M.; Kögerler, Paul
Abstract Mixed‐valence polyoxovanadates(IV/V) have emerged as one of the most intricate class of supramolecular all‐inorganic host species, able to encapsulate a wide variety of smaller guest templates during their self‐assembly formation process. As showcased herein, the incorporation of guests, though governed solely by ultra‐weak electrostatic and van der Waals interactions, can cause drastic effects on the electronic and magnetic characteristics of the shell complex of the polyoxovanadate. We address the question of methodology for the magnetochemical analysis of virtually isostructural VIV/V22O54‐type polyoxoanions of D2d symmetry enclosing diamagnetic VO2F2− (C2v), SCN− (C∞v), or ClO4− (Td) template anions. These induce different polarization effects related to differences in their geometric structures, symmetry, ion radii, and valence shells, eventually resulting in a supramolecular modulation of magnetic exchange between the V(3d) electrons that are partly delocalized over the V22O54 shells. We also include the synthesis and characterization of the novel [VVO2F2@HVIV8VV14O54]6− system that comprises the rarely encountered discrete difluorovanadate anion as a quasi‐isolated guest species.